2013
DOI: 10.1016/j.renene.2012.09.011
|View full text |Cite
|
Sign up to set email alerts
|

2.5D large eddy simulation of vertical axis wind turbine in consideration of high angle of attack flow

Abstract: A renewed interest in vertical axis wind turbines (VAWTs) has been seen recently. Computational fluid dynamics (CFD) is regarded as a promising technique for aerodynamic studies of VAWTs. In particular, 2D unsteady Reynolds-averaged Navier-Stokes (URANS) is commonly adopted, although past studies on VAWTs revealed the limited accuracy of 2D URANS. This paper investigated the feasibility and accuracy of three different CFD approaches, namely 2D URANS, 2.5D URANS and 2.5D Large Eddy Simulations (LES), in the aer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
116
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(119 citation statements)
references
References 30 publications
3
116
0
Order By: Relevance
“…Numerous authors [11,13,18] have suggested that 3D CFD models are not practical for turbine performance investigations due to their excessive simulation time and computational requirements.…”
Section: Numerical Simulation Timementioning
confidence: 99%
See 2 more Smart Citations
“…Numerous authors [11,13,18] have suggested that 3D CFD models are not practical for turbine performance investigations due to their excessive simulation time and computational requirements.…”
Section: Numerical Simulation Timementioning
confidence: 99%
“…It has previously been suggested that URANS methods are unable to accurately predict vertical axis turbine blade vortex shedding and flow diffusion, requiring higher order CFD methods such as Large Eddy Simulation (LES) [13]. However the authors believe that the accuracy of 3D CFD simulations when compared to EFD results, as demonstrated in Figure 10, suggests that reasonable estimates of performance coefficients such as Cp can be obtained by URANS methods and that resolution of small- …”
Section: Validation Of Numerical Simulations With Experimental Fluid mentioning
confidence: 99%
See 1 more Smart Citation
“…The TSR, which is also referred to as λ in the manuscript, is defined as U/V ∞ , where U is the tip peripheral velocity of the rotor, namely ωR, ω is the angular velocity of the blade and R the rotor radius, while V ∞ is the free stream velocity. A 2.5D model [16] is also presented in the literature, which differs from a 3D simulation, because only a segment of the airfoil blades is modeled with periodic boundaries at the extremities of the domain. The limitation of this model is that it can only be used with Darrieus-type straight-bladed VAWT.…”
Section: Introductionmentioning
confidence: 99%
“…Simulations of VAWT noise emissions from first principles would require an accurate determination of the flow close to the blade, which is a computationally expensive task. However, recent progress with large eddy simulations [10][11][12][13][14] might render this approach feasible further on.…”
Section: Introductionmentioning
confidence: 99%